2012
DOI: 10.1371/journal.pmed.1001260
|View full text |Cite
|
Sign up to set email alerts
|

HIV Treatment as Prevention: The Utility and Limitations of Ecological Observation

Abstract: Results from several observational studies of HIV-discordant couples and a randomized controlled trial (HIV Prevention Trials Network 052) show that antiretroviral therapy (ART) can greatly reduce heterosexual HIV transmission in stable HIV-discordant couples. However, such data do not prove that ART will reduce HIV incidence at the population level. Observational investigations using ecological measures have been used to support the implementation of HIV treatment for the specific purpose of preventing transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 93 publications
1
46
0
1
Order By: Relevance
“…HIV scientists, including the HPTN052 investigators, have cautioned against too many expectations Smith et al, 2012). In parallel, some social researchers have asked what is being ignored 'in the rush to paradigm shift, game-change, rollout and scale-up' (Nguyen et al, 2011, p. 2).…”
Section: Concluding Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV scientists, including the HPTN052 investigators, have cautioned against too many expectations Smith et al, 2012). In parallel, some social researchers have asked what is being ignored 'in the rush to paradigm shift, game-change, rollout and scale-up' (Nguyen et al, 2011, p. 2).…”
Section: Concluding Reflectionsmentioning
confidence: 99%
“…A central concern includes the potential impact of TasP and other biomedical prevention technologies on established prevention methods, such as condom use, and increases in sexual risk practices, or 'risk compensation' (Chen, 2013;Eaton & Kalichman, 2007). Some have cautioned against overly optimistic expectations, citing examples of settings with high treatment coverage, such as Australia, and the 'apparent ineffectiveness' of these 'natural TasP experiments' in reducing actual HIV incidence (Phillips et al, 2013;Smith, Powers, Muessig, Miller, & Cohen, 2012;Wilson 2012, p. 2). Others warn against 'hyperbole' (Dowsett, 2013) or argue that TasP presents a troubling 'remedicalization' of the epidemic (Nguyen, Bajos, Dubois-Arber, O'Malley, & Pirkle, 2011) that will be ineffective if it disregards the myriad social factors that shape sexual practices, prevention and treatment uptake (Adam, 2011;Kippax & Stephenson, 2012;Kippax, Reis, & de Wit, 2011;Persson, 2013).…”
mentioning
confidence: 99%
“…[14][15][16][17][18] In British Columbia, where researchers have stated that treatment as prevention has led to a decrease in total HIV transmissions, 1 HIV incidence among MSM reportedly "increased by 13% from 2005 to 2008." 4 Confounding factors affecting HIV transmission, such as Vancouver's safe injection site, needle exchange and peer-based prevention strategies, may have played a role in reducing overall HIV incidence in British Columbia, thus limiting conclusions about the extent to which treatment as prevention can prevent HIV transmission at the population level. 4 Similar debates have occurred in San Francisco, where some have argued that stabilized rates of HIV transmission among MSM are exclusively the result of antiretroviral therapy, 2 with others asserting that the relatively stabilized HIV incidence is due to a combination of serosorting and increased HIV-status awareness 19 (where serosorting is the practice of engaging in sexual activities that can transmit HIV only with partners of concordant HIV status, either as total serosorting [a person has sex only with those whose HIV status is concordant] or as condom serosorting [a person bases the decision to use a condom on concordance or discordance of the other person's HIV status]).…”
Section: Does All Evidence Support Treatment As Prevention?mentioning
confidence: 99%
“…T he potential for antiretroviral therapy to reduce HIV transmission, a strategy known as "treatment as prevention," [1][2][3][4] is important in light of unrelenting HIV transmission. The Public Health Agency of Canada has estimated that the number of new cases of HIV infection in Canada in 2014 was 2570 (range 1950-3200), marginally lower than in previous reports.…”
mentioning
confidence: 99%
“…Ecological studies have shown confl icting results regarding the impact of ART scale-up on HIV incidence. [7][8][9][10] The only nonecological evidence of the population-level effect of increasing ART coverage comes from a prospective population cohort in KwaZulu-Natal, South Africa. Controlling for behavioral, demographic, economic, and environmental risk factors, individual HIV acquisition risk declined signifi cantly with increasing ART coverage both in the surrounding community 11 and among household members of the opposite sex.…”
mentioning
confidence: 99%